Cost-effectiveness and affordability evaluation of a residential prototype built with compressed earth bricks, hybrid roofs and palm midribs - Abdel Gelil Mohamed, Nermine; Abo Eldardaa Mahmoud, Islam (Frontiers in Built Environment, 2023)
As a response to rising housing prices and the high cost of materials in the building and construction industry, a rural prototype house (the Ecofordable House) was built with alternative technologies. The house is located in the western desert zone of Giza, Egypt, and features enhanced vernacular technologies with local materials. Interlocking compressed stabilized earth brick walls, partially reinforced, jack arch and funicular shell roofs, and date palm midribs were employed in an attempt to reduce the usage of steel, fired bricks, cement, and imported wood. The present research evaluates the house’s construction cost-effectiveness and affordability through detailed real-world data and comparisons of material quantities, labor, and costs with those of conventional methods. The “price-to-income ratio” is used as an indicator of affordability. According to the findings, walls cut costs by half, roofs by a quarter, and midribs by two-thirds; the alternatives combined saved 45%, and the house saved a quarter of the cost after adding common expenses. Moreover, less than one-third of steel, fired bricks, and cement were utilized. In the Egyptian context of government-built houses, the prototype would be affordable for most Egyptian income brackets while the conventional house was expensive for the lowest three. The findings provide empirical support for the economic advantages of enhanced vernacular technologies as alternatives and address residential affordability in similar contexts.